Pengaruh Financial Leverage, Earnings per Share, dan Dividend per Share terhadap Harga Saham - Rusliati, Ellen; Prasetyo, Galih (Jurnal Trikonomika, 2011)
This researchs puposes are to know the Financial Leverage, Earnings per Share (EPS), Dividend per Share (DPS), stock price, and the level of influence Financial Leverage, Earnings per Share (EPS) and Dividend per Share (DPS) partially or simultaneously to the stock price. Research methods used are descriptive and verificative. Methods of analysis used are multiple linear regression, correlation, and coefficient of determination. Simultaneous hypothese is tested through F test and partial hypotheses are tested through t test. Annual data are obtained from the Indonesian Stock Exchange.Financial leverage trend is decreasing, while EPS, DPS, and stock price trends are increasing. Financial Leverage, Earnings per Share (EPS) and Dividend per Share (DPS) simultaneously have influence on stock price in manufacturing companies listed on the Indonesian Stock Exchange amounted to 75.17% in 2006-2008. Financial Leverage partially did not affect stock prices significantly, while Earnings per Share (EPS) has positive effect and significant with determination coefficient of 54.4%, and Dividend per Share (DPS) 20.7%.